Construction Management of Jati Weir Rehabilitation (Channel Madiun Irrigation Area) Magetan Regency with Value Engineering & Scheduling Implementation Management Planning - Hadi, Suprapto; Oetomo, Wateno; Wulandari, Esti (Green Publisher Indonesia, 2022)
One of the infrastructure developments in the region that will soon be implemented is the construction of the Jati Weir rehabilitation construction project which is the main dam in the Madiun Irrigation Area (DI SIM) Main Channel in Magetan Regency. In order to maximize the results of cost and time, it is necessary to have a flexible technique or management in the work of this project. The method used to determine alternative types of construction that are efficient and effective in terms of cost and time is the application of Value Engineering in the Jati Weir rehabilitation planning work. Then to get the most effective and efficient time needed for the construction of the rehabilitation of the Jati Weir is done by analyzing the needs of time, labor and tools and the results of the analysis are included in the preparation of a work schedule with the help of Microsoft Project Manager 2021 software. The results of the Value Engineering analysis are the work items that can be done are the still pond items; The existing construction is a random pile of concrete blocks in the form of 1x1x0.5 m blocks with alternatives given to replace the existing construction are 1000 kg tetrapod concrete blocks and 1000 kg dolos concrete blocks; the selected alternative is 1000 kg dolos concrete blocks with a manufacturing and installation cost of Rp. 16,239,115,273.27. 16,239,115,273.27; The cost value of making and installing 1000 kg of dolos concrete blocks is reduced by Rp. 6,252,816,421.53 from the existing construction value; The overall total cost changes from Rp. 62,420,557,268.77 (excluding VAT/VAT) to Rp. 56,167,740,847.24 (excluding VAT/VAT) after Value Engineering. For the implementation schedule plan, the time for Preparatory Work takes a total of 42 working days and for the Jati Weir Rehab Work takes a total of 185 working days. The work is planned to start from March 01, 2023 and end on November 29, 2023.